New crustacean microcoprolites of the Upper Triassic limestones of the Sambosan Accretionary Complex, Japan - Senowbari-Daryan, Baba; Chablais, Jérome; Martini, Rossana (Journal of Paleontology, 2010)
We report here the first crustacean microcoprolites from the Sambosan Accretionary Complex (AC) in Japan. Three species of crustacean (order Decapoda) microcoprolites - <span class="italic" style="box-sizing: border-box; margin: 0px; padding: 0px; border: 0px; font-style: italic; font-variant-numeric: inherit; font-variant-east-asian: inherit; font-stretch: inherit; line-height: inherit; font-family: "Noto Sans", Helvetica, Roboto, Arial, sans-serif; font-size: 13px; vertical-align: baseline; color: rgb(89, 89, 89);">Payandea japanica n. sp., <span class="italic" style="box-sizing: border-box; margin: 0px; padding: 0px; border: 0px; font-style: italic; font-variant-numeric: inherit; font-variant-east-asian: inherit; font-stretch: inherit; line-height: inherit; font-family: "Noto Sans", Helvetica, Roboto, Arial, sans-serif; font-size: 13px; vertical-align: baseline; color: rgb(89, 89, 89);">Favreina tosaensis n. sp., and a species belonging to the genus <span class="italic" style="box-sizing: border-box; margin: 0px; padding: 0px; border: 0px; font-style: italic; font-variant-numeric: inherit; font-variant-east-asian: inherit; font-stretch: inherit; line-height: inherit; font-family: "Noto Sans", Helvetica, Roboto, Arial, sans-serif; font-size: 13px; vertical-align: baseline; color: rgb(89, 89, 89);">Parafavreina? sp. are described from the Late Carnian to Rhaetian shallow-water limestones of the Sambosan AC, which were originated on extinct and subsiding volcanoes forming a mid-oceanic atoll-type buildup in the Panthalassan Ocean. Coprolites, which occur within a lagoonal to back-reef facies, provide new insight into the micropaleontology and sedimentology of the Sambosan limestones. Their presence in this tropical shallow-water depositional setting heightens their status of sedimentary facies indicators of such environments. Furthermore the occurrence of these Tethyan coprolites genera in Japan improves our knowledge of the distribution of Triassic crustacean decapods across the Panthalassan Ocean.
UnivIS-Import:2017-11-07:Pub.2010.nat.dgeo.IGM.LP.newcru
Keywords: Coprolites; Japan; Limestone; Panthalassa; Triassic